Pengaruh Lagu Bahasa Arab Dengan Menggunakan Media Audio Visual Terhadap Penguasaan Mufradat Pada Siswa Madrasah Diniyah Children Darut Taqwa Purwosari Pasuruan - Nurrokhmatulloh; Nur Khamidah, Nanda (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
Madrasah Diniyah Children Darut Taqwa is a special Madrasah for early children where the learning focuses on religious materials and also coaching for early children. The purpose of study this is to the know about implementation and effect of arabic song by visual audio the mastery of student vocabulary that include the addition new vocabulary and translated. This research used quantitative approach, the type of research used is pre-experimental (one group pretest posttest) with a population of 27 students. The instruments that used in this research are observation, test (pretest and postest) and documentation.There is high significant influence in improved the master of student's. It is based on final result the average score before the treatment is 47.11 and after the average treatment of postest score increased to 88.52. From T-test results with DF = 26 with significant level 0.05 amounting to 2.055, and obtained count = 15.818. Because Tetung> Ttabel, and then 15,818> 2.055 then Ho is rejected and Ha accepted. So it can be concluded there is effect of Arabic song’s with visual audio to the mastery vocabulary student the Madrasah Diniyah Children Darut Taqwa.